Effect of protein concentrate supplementation on the composition of amino acids in milk from dairy cows in an organic farming system - Pavel Horký (Potravinarstvo, 2017)
Our experiment examined the effect of feeding a protein concentrate supplement on the composition of amino acids in milk from dairy cows managed in an organic farming system. The experiment included two groups of cows. Animals in both groups received an identical basic feed ration composed of maize silage, clover-grass haylage from the first cutting, grass haylage from the first cutting, winter wheat and spring barley. The first group of dairy cows (n = 10) served as a control without the addition of protein concentrate to the feed ration. The second experimental group (n = 10) received in addition to the basic feed ration a protein concentrate composed of soybean, sunflower and linseed cakes at rate 1 kg per head per day. The experiment lasted 30 days. Milk analysed for amino acid content was sampled at 10-day intervals. Addition of the protein concentrate significantly increased milk contents of aspartic acid, proline, threonine, glycine, alanine and glutamic acid. A significant decrease of valine also was recorded in milk from the experimental group. The results of our experiment show that a protein concentrate supplement can affect concentrations of some amino acids in milk from dairy cows.